Synthesis and Investigation of Macromolecular Photoswitches - Pang, Juan; Kong, Jingyang; Xu, Jialing; Mao, Xincheng; Hu, Xiaohong (Frontiers in Materials, 2020)
TThe photo-isomerization characteristic made azobenzene to be a kind of potential molecule as a photo switch in material fields. However, lack of stability for cis isomer and its photobleaching characteristic restricted its further application as a photo switch. Therefore, we designed two polymers containing azobenzene (AZO) domain as macromolecular photoswitches and investigated their switching performance. Hydrophilic monomers like hydroxyethyl methylacrylate (HEMA) and N-Vinyl-2-pyrrolidone (NVP) were chosen to copolymerize with AZO monomer to form HEMA-AZO copolymer and HEMA-NVP-AZO terpolymer by radical polymerization. Domain content was calculated by integration of each peak of 1H NMR spectrum. Real-time UV spectra of polymers response to UV light confirmed quick and successful trans-to-cis transition for AZO domain. In reverse, the operable recovery processes induced by white light were also verified by real-time UV spectra. Furthermore, repeating irradiation by UV light and white light for 20 times were used to check their fatigue resistance and recyclability. More importantly, recovery behaviors for two polymers could be adjusted by many factors like solvent property, environment temperature and light intensity. Higher environment temperature or higher light intensity resulted in shortened recovery time. But the influence of solvent was a little different for two polymers. Finally, nanoassembles formed by HEMA-NVP-AZO terpolymer and poly(β-CD)(or poly(α-CD)) exhibited similar controllable switching performance to pure polymer. In brief, the effectiveness and efficiency of polymers as photoswitches had been confirmed by results in the research.